2020
DOI: 10.3389/fneur.2020.581186
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Motor Recovery in the Upper Extremity for Repetitive Transcranial Magnetic Stimulation and Occupational Therapy Goal Setting in Patients With Chronic Stroke: A Retrospective Analysis of Prospectively Collected Data

Abstract: Recovery from motor paralysis is facilitated by affected patients' recognition of the need for and practice of their own exercise goals. Neurorehabilitation has been proposed and used for the treatment of motor paralysis in stroke, and its effect has been verified. If an expected score for the neurorehabilitation effect can be calculated using the Fugl-Meyer Motor Assessment (FMA), a global assessment index, before neurorehabilitation, such a score will be useful for optimizing the treatment application criter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 51 publications
(67 reference statements)
1
21
0
1
Order By: Relevance
“…For improvement of the FMA, it has been reported that baseline motor function predicts motor function recovery following various interventions, such as constraint-induced movement therapy (CIMT), repetitive transcranial magnetic stimulation (rTMS), transcranial direct current (rTMS), transcranial direct current stimulation (tDCS), and robot therapy (RT). 36 41 This study using NMES also suggested that baseline motor function predicted motor function recovery, as in these previous studies.…”
Section: Discussionsupporting
confidence: 77%
“…For improvement of the FMA, it has been reported that baseline motor function predicts motor function recovery following various interventions, such as constraint-induced movement therapy (CIMT), repetitive transcranial magnetic stimulation (rTMS), transcranial direct current (rTMS), transcranial direct current stimulation (tDCS), and robot therapy (RT). 36 41 This study using NMES also suggested that baseline motor function predicted motor function recovery, as in these previous studies.…”
Section: Discussionsupporting
confidence: 77%
“…Table 1 provides an overview of included studies, and Figure 3 illustrates the variation in study design, rTMS protocol, time post-stroke and number of sessions across studies. Half of the included studies (13/26), encompassing a large majority of the patient population, were single-arm, non-randomized retrospective or prospective studies (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)36). Eleven studies included a sham-control condition either in a crossover or parallel-group design (16,20,(33)(34)(35)(37)(38)(39)(40)(41)(42).…”
Section: Resultsmentioning
confidence: 99%
“…In terms of rTMS protocols, 10 studies used excitatory rTMS (17,21,22,33,34,36,39) or iTBS (18,37,38) targeting ipsilesional M1 (17,18,21,22,34,(36)(37)(38)(39) or ipsilesional S1 (33), with either a single session (18,33,34,36,37,39) or a total of 10 sessions (17,21,22,38) of intervention. A total of 13 studies used inhibitory rTMS over contralesional M1, with a range from 5 up to 30 intervention sessions (19,20,(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)41). Two studies used both inhibitory contralesional, as well as excitatory ipsilesional rTMS over M1 (35,40), and a single study measured the effects of a single session of excitatory contralesional rTMS on M1, dorsal premotor cortex (dPMC), and anterior intraparietal sulcus (aIPS) (16).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is of note that the procedures for determining a responsiveness metric differ across studies and there is no unique and universally accepted way. Some examples are computing absolute (delta) or relative changes (percentage, ratio) to control stimulation (e.g., [26]) or to baseline (e.g., [27,28]), reporting of proportional change (e.g. [29]), applying cut-off-based procedures (median split e.g., [27], splitting based on the minimal clinically important difference e.g., [30]) towards more complex approaches such as the use of composite scores (e.g.…”
Section: Introductionmentioning
confidence: 99%